«Nostalgieria»: Derrida przed i po Frantzu Fanonie - Farred, Grant (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
Monolingualism ofthe Other; or, The Prosthesis of Origin (MO) Jacques Derrida (1998) takes up Frantz Fanon's project in The Wretched of the Earth (WE) at its very core. Derrida thinks "decolonization" from the very place for which Fanon— and from which Derrida, symbolically and metonymically—struggled and wrote, Algeria. The author explores the experience of writing "nostalgerically."
Keywords: Derrida; Fanon; nostalgeria; monolingualism